An Analysis On Students’ Difficulties in Changing Active to Passive in Writing For Tenth Grade at SMAN 21 - Rindu Kaya Sinambela; Yessy Octavianna; Nurhayati Sitorus (Jurnal Pendidikan LLDIKTI Wilayah 1 (JUDIK), 2025)
Based on the results of observations made by researcher at SMA Negeri 21 Medan, researcher found several mistakes made by students in changing active sentences into passive, such as "Tika ate an apple yesterday." some of students answered "An apple has eaten by Tika yesterday," while others some answered "An apple was ate by Tika yesterday." It should read, "An apple was eaten by Tika yesterday." From the background of the problems found, the researcher was interested in conducted this research. This research used a qualitative descriptive approach. Data was gathered by analyzing the results of interviews and written texts by ten-eighth-grade from 32 students. The results of the interviews showed that students had trouble identifying both subjects and objects, difficulty in utilizing the auxiliary verb "to be," and switching between the active voice to Verb 3 in the form of the passive voice. In the written text results, 19 dominant students made errors in utilizing the auxiliary verb “be”, 10 dominant students made problems in distinguishing between past tense and past participle, and 3 dominant students made errors in both. The aim of this research was to determine students' difficulties in changing active sentences to passive.